2012
DOI: 10.1097/ta.0b013e318249a97c
|View full text |Cite
|
Sign up to set email alerts
|

Milk fat globule epidermal growth factor-factor 8 mitigates inflammation and tissue injury after hemorrhagic shock in experimental animals

Abstract: Background Insufficient clearance of apoptotic cells leads to increased inflammation and exaggerated organ injury. The opsonizing protein, milk fat globule EGF-factor 8 (MFG-E8), upregulates apoptotic cell clearance. The purpose of this study was to determine the degree of apoptotic cell clearance, and if inflammation, organ injury and survival are improved following treatment with recombinant human MFG-E8 (rhMFG-E8) after hemorrhagic shock. Methods Male mice underwent a pressure-controlled (25±5 mmHg) model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…It is also possible that the human form of MFG-E8 may be less potent in the mouse, as the homology between human and mouse MGF-E8 is only 56%. Nevertheless, rhMFG-E8 is clearly active in rodents, as we have demonstrated previously [31][32][33][34][35] and in the present study. Therefore, rhMFG-E8 is expected to have comparable beneficial effects in humans with IBD.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…It is also possible that the human form of MFG-E8 may be less potent in the mouse, as the homology between human and mouse MGF-E8 is only 56%. Nevertheless, rhMFG-E8 is clearly active in rodents, as we have demonstrated previously [31][32][33][34][35] and in the present study. Therefore, rhMFG-E8 is expected to have comparable beneficial effects in humans with IBD.…”
Section: Discussionsupporting
confidence: 66%
“…[31][32][33][34][35] We have injected mice with up to 2560 μg/kg rhMFG-E8 intravenously, and observed no alteration in liver transaminases (AST and ALT) 24 h later (unpublished observations). More comprehensive studies, however, will need to be conducted to exclude any toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MFGE8 may form a bridge to connect with phagocytic cells and apoptotic cell. It has been reported that exogenous MFGE8 attenuated inflammation injury by increasing apoptotic cell clearance in various model, including cerebral ischemic injury (Cui et al, 2010; Kranich et al, 2010; Lauber et al, 2013; Matsuda et al, 2011b; Wu et al, 2012; Zhang et al, 2012). In the present study, rhMFGE8 reduced the expression of the apoptosis executor cleaved caspase 3, and knockdown of endogenous MFGE8 potentiated the expression of cleaved caspase 3 after SAH.…”
Section: Discussionmentioning
confidence: 99%
“…HB-EGF likely promotes its beneficial effects in multiple fashions, including promoting integrin-extracellular matrix interactions as well as intercellular adhesions (74) and preventing intestinal stem cells from injury under pathological conditions (75). Additionally, milk fat globule-EGF factor 8 also improves survival in both CLP and hemorrhagic shock and decreases both inflammation and tissue injury although its impact on intestinal permeability is unknown (76;77). …”
Section: Intestinal Epithelium – a Selective Barriermentioning
confidence: 99%